ANALISIS RETURN ON INVESTMENT (ROI) DAN RESIDUAL INCOME (RI) DENGAN PENDEKATAN DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN PADA PT. GUDANG GARAM Tbk. YANG TERDAFTAR DI BURSA EFEK INDONESIA - Erviva Fariantin; Hengki Samudra (Valid: Jurnal Ilmiah, 2019)
This study aims to determine a company's financial performance as measured using the Return On Investment with Du Pont System approach. To determine a company's financial performance as measured using the Residual Income. Objects in this study conducted at the company PT Gudang Garam Tbk. The data used in this research is secondary data obtained from the Indonesia Stock Exchange. The data in the form of financial statements ie balance sheet and profit/loss taken in the annual report. These results indicate that the ability of companies in the process of return on investment is not setabil by showing the percentage up and down each year for research provide. It shows that the company has not been able to optimize the return on sales and investments are undertaken each year, but if in view of the general standard or average industry company's ability to return on investment can say either as a result of the calculation of ROI analysis of more value of the general standard or average industry. Meanwhile, when viewed from the calculation of residual income (RI), obtained a positive value RI. With positive RI means that the company is able to generate economic added value for shareholders and investors. It shows also that the financial performance in doing is effective and efficient (RI> 0)